Problematika Pembuktian dan Daluarsa dalam Penuntasan Pelanggaran HAM 1965–1966 - Sinaga, Wahyu; Zukriadi, Diki (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
The 1965–1966 tragedy was one of the most systematic gross human rights violations in Indonesian history, involving mass killings, arbitrary detentions, torture, and enforced disappearances. This study highlights two major obstacles to its resolution: evidentiary challenges and the statute of limitations, along with tensions between national and international legal frameworks. The research employs a qualitative descriptive method through literature review. Findings indicate that evidentiary barriers are structural, while international law rejects the statute of limitations for crimes against humanity. The study recommends harmonizing national laws with international standards, establishing a truth commission, and implementing transitional justice to achieve accountability and restore victims’ rights.